Sustainable alkaline activation of fly ash, aluminium anodising sludge and glass powder blends with a recycled alkaline cleaning solution. (20th April 2019) - Cristelo, Nuno; Fernández-Jiménez, Ana; Castro, Fernando; Fernandes, Lisete; Tavares, Pedro
Highlights: Incorporation of uncommonly used industrial waste improved FA-based geopolymer. Commercial sodium hydroxide was successfully replaced by disposed solution. Addition of glass powder and aluminium sludge increased initial reaction rate. Presence of sulphur didn't seem to have a negative impact on final strength. Abstract: Introduction of new residues and wastes in the development of alkaline activated materials is a major concern regarding the spreading and dissemination of this technique. Such increase in the spectrum of available raw materials will decrease the need for long-distance transportation of the more traditional precursors that have been tirelessly used in the past two decades (e.g. fly ash, blast furnace slag). Additionally, the use of commercial activators severely hinders its environmental and financial performance, promoting the need to develop waste-based activators. In this paper, wastes from the aluminium anodising and extrusion processes and from the production of optical lenses were combined with low-calcium fly ash, to produce binders exclusively made from wastes and residues. The performance was assessed through uniaxial compression strength tests, which were accompanied by the monitorisation of several physical properties, including temperature, pH and weight; and by a thorough microscopic analysis, including scanning electron microscopy, coupled with energy dispersive spectroscopy, and x-ray diffraction, for mineralogy characterisation. Results show that the addition of glass powder and aluminium anodising sludge to class-F fly ash optimised the final precursor, which was then successfully activated with a disposed solution, originally used to clean the aluminium extrusion steel dies. The inclusion of soluble silicon and aluminium in the precursor raised the compression strength after short-term curing, compared with pastes prepared only with fly ash.